Public and Private Law Boundaries, Nexus of Position Within State Owned Corporation in Indonesia Perspective - et al., Arie Sudihar (International Journal of Advanced Science and Technology, 2019)
Globalization changing corporation how they acting, how they process, how they comply, and how they seeing opportunity. Vast change of corporation process made hard to indistinct private and public process of each corporation action. State Owned Corporation that came from public need in private bodies being place by government to serve duality need. In one side they tool for government to do their public obligation, but in other hand they tool to get more national income aside of tax and customs. This condition lead to question are State Owned Corporation private or public? Sometimes State Owned Corporation action see with private lens but in other time public lens being used. Indonesia seeing this duality of State Owned Corporation as place of merge between public law such as Maladministration, Corruption, and Liability of Public Official with private law such as Piercing Corporate Veil, laissez-Faire, and Corporate Liability.  Through this paper, we will discuss how the relationship between public law and private law in the State Owned Corporation. With a qualitative approach using regulatory as a tool to measure crosses from public law and private law, we can see how merging of two law concept being merge as nexus of law within Indonesia State Owned Corporation.